Quality control product for folate metabolism related gene detection as well as preparation method and application of quality control product - DENG YONG; QIN QIONGYAO; DENG ZHONGPING; DAI LIZHONG; ZHOU MIN (2023)
The invention belongs to the field of gene detection, and particularly relates to a quality control product for folate metabolism related gene detection and a preparation method and application thereof. In order to solve the problem of lack of MTRR genotyping quality control products in the field, the invention provides a quality control product for folate metabolism related gene detection. The quality control product can comprise nine types of quality control products including a wild type, a heterozygous mutant type and a homozygous mutant type of the MTHFR gene C677T and the MTRR gene A66G, takes tumor cell line DNA as a raw material, is low in price, short in period, high in accessibility and good in stability, contains a complete human genome background and has good intercommunity with a clinical sample. 本发明属于基因检测领域，具体涉及一种用于叶酸代谢相关基因检测的质控品及其制备方法与应用。为解决本领域缺少MTRR基因分型质控品的问题，本发明提供了一种用于叶酸代谢相关基因检测的质控品。所述质控品可以包含MTHFR基因C677T和MTRR基因A66G的野生型、杂合突变型及纯合突变型共9种型别的质控品，以肿瘤细胞系DNA为原材料，价格低廉，周期短，可及性高，稳定性佳，包含完整的人基因组背景，与临床样本具有良